Cancer in Women in Kerala - a Transition from a Less-developed State - P Jayalekshmi, P Gangadharan, K S Mani (Asian Pacific Journal of Cancer Prevention, Vol 7, 2006, 2006)
An epidemiologic assessment of the problem of cancer in women in Kerala based on 3 Population Cancer Registry data and a Hospital Based data is presented. Kerala's Socio-economic and demography presents an intermediate development from a less developed to a better-developed state. As yet, the women follow a tradition-based life style. Cancer incidence rate in Kerala was only 80 per cent of urban rates than seen in Urban Metropolis in India. The pattern of site distribution has shown that GI, Breast & Cervix cancers are the predominant cancers. Oral cavity cancers also show a high frequency. Thyroid cancer has a higher incidence rate in Kerala compared to other areas. Lung cancer among women has higher incidence rate in Karunagappally women. A high prevalence of tobacco use is reported among the men in the above area. Breast cancer incidence rate in the rural areas was only 60 per cent of the rate seen in Urban Trivandrum. Unlike in other rural and urban areas of India Cervix cancer has a low incidence rate in Kerala women. This may be due to better education and also due to the changes in marital and other life style practices. Only 15 per cent of cancer patients attend for medical assistance in localized stage of disease. The need for public education is highlighted and focusing on tobacco use control, self-examination and screening